Love, friendship and the self intimacy, identification, and the social nature of persons - Helm, Bennett W. (Oxford : Oxford University Press, 2010)
Bennett Helm re-examines our common understanding of ourselves as persons in light of the phenomena of love and friendship. He argues that the individualism that is implicit in that understanding cannot be sustained if we are to understand the kind of distinctively personal intimacy that love and friendship involve.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Love -- Philosophy; Friendship -- Philosophy; Emotions (Philosophy); Identity (Philosophical concept)